ソウヤ センジョウ ニオケル 2.5 Mc/s クウデン ザツオン キョウド ノ カンソク ケッカ - 石沢, 薫; イシザワ, カオル; 若井, 登; ワカイ, ノボル; 長谷川, 貞雄; ハセガワ, サダオ; 川尻, 矗大; カワジリ, ノブヒロ; ISHIZAWA, Kaoru; WAKAI, Noboru; HASEGAWA, Sadao; KAWAJIRI, Nobuhiro (国立極地研究所, 1962)
P(論文) Field intensity of atmospheric radio noise on 2.5Mc/s was measured on board the "SOYA" along the course from Tokyo to Antarctica. Results of the analysis of the measurements are summarized as follows: 1) The daytime noise intensity which is predominant in the tropical region and near South Africa corresponds well to the meteorological situation. 2) Atmospheric radio noise intensity measured on board the "SOYA" agrees well with the values predicted on the "Noise Map" prepared by CRPL and with the result of measurement at the fixed stations (Singapore and Pretoria). 3) Characteristics of the atmospheric radio noise were examined in connection with the solar zenith angle and the latitude. Both the mode of diurnal variation and the relation between absorption and solar zenith angle very distinctly with the latitude. 4) Decrease in the intensity at midnight towards the south from about 32°S is greater than that of the intensity calculated only from the distance (the so-called unabsorbed field intensity) and smaller than what was predicted on the CRPL's map. 5) Abnormal enhancement of the radio noise was seen when the ship went under the pouring rain, while the noise fell down to zero level with a flash of lightning, and then it rose exponentially with the time constant of the order of 1 minute. These facts seem to suggest the mechanism how the atmospheric radio noise originates in rain falls. In other words, the precipitation noise due to rainfall occurs in the presence of both raindrops and the static field between the earth and the cell of charged clouds. departmental bulletin paper